A comparison of ALK gene rearrangement and ALK protein expression in primary lung carcinoma and matched metastasis. Issue 2 (5th May 2017) - Trejo Bittar, Humberto E; Luvison, Alyssa; Miller, Caitlyn; Dacic, Sanja
Abstract : Aims: The 2013 College of American Pathologists, the Association for Molecular Pathology and the International Association for the Study of Lung Cancer guideline for EGFR and ALK testing in lung carcinoma indicates that either the primary tumour or the metastasis is suitable for testing. The heterogeneity of gene mutations has been studied extensively, while similar reports on gene rearrangements are limited. The aim of this study was to determine if ALK status between primary tumour and matched metastasis differs. Methods and results: Fifteen ALK fluorescence in‐situ hybridization (FISH) rearranged and 19 non‐ ALK FISH rearranged adenocarcinomas were collected retrospectively based on availability of tissue from a matched metastatic site. Sixty‐eight samples were tested by ALK FISH (Vysis ALK break‐apart FISH kit) and ALK immunohistochemistry (IHC) (Ventana ALK D5F3 CDx assay). Overall agreement of FISH and IHC was 88%, with IHC showing 100% specificity and 71% sensitivity. Concordance between primary site and metastasis by ALK FISH was seen in 30 cases (88%), and in 32 cases (94%) by ALK IHC. Five discordant cases were found (15%). Three ALK FISH discordant cases had low percentage of ALK FISH‐positive tumour cells (average 23%, range: 18–31%) and all were negative by ALK IHC. One IHC discordant case had a high percentage of ALK FISH‐positive tumour cells (67%), and was ALK IHC‐negative. One FISH discordant case showed ALK FISH‐ and ALK IHC‐positive primary tumour, but ALK FISH‐ and ALK IHC‐negative metastasis. Conclusions: ALK FISH results show more frequent discordances between primary tumour and matched metastases than ALK IHC, due probably to technical challenges and sample quality. This observation indicates that the quality of sample and technical expertise of the laboratory should guide the decision about ALK testing in clinical practice.